It Should Not Be a Pit Stop: Voices and Perspectives of Homeless Youth on Labeling and Placement in Special Education. Issue 2 (3rd April 2017) - Saldanha, Kennedy
ABSTRACT: Although the incomplete school histories of homeless youths are often highlighted, little is written about their school careers involving special education. This study is based on the educational narratives of homeless youths in special education. Their narratives were constructed using "direct scribing" and narrative ethnography. The article highlights the stigma and bullying experienced by youths as a result of being labeled, and shares their perspectives about special education being similar to a "pit stop"—a brief transitory stop with very short-sighted designs and benefits. It also discusses the benefits of direct scribing and the need to listen to the perspectives of students themselves on how labeling and placement in special education affect them.